2019
DOI: 10.1055/s-0039-1693454
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient Flap Monitoring after Deep Inferior Epigastric Artery Perforator Flap Breast Reconstruction: How Long Is Long Enough?

Abstract: Background There is a growing trend across health care to perform increasingly complex procedures in less acute settings. This shift has been fueled, in part, by enhanced recovery protocols, which have shortened hospital stays after major surgeries. We set out to determine the timing of microvascular complications after deep inferior epigastric artery perforator (DIEP) free flap breast reconstruction in a high-volume practice using continuous flap monitoring technologies. Methods The medical charts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 30 publications
0
23
0
1
Order By: Relevance
“…Previous studies used monitoring windows with varying durations, mostly between 24 and 48 h postoperatively [1,17,22]. A recent study by Carruthers et al showed that microvascular issues become visible during clinical evaluation in the initial 23 h following reconstructive surgery [23], suggesting that a 24-h time window should be adequate. These results in combination with the results of the current study suggest that continuous postoperative monitoring of the DIEP flap with the use of tissue oximetry for longer than 24 h would not provide additional important information and therefore a timeframe of 24 h of continuous postoperative tissue oximetry monitoring could be justified.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies used monitoring windows with varying durations, mostly between 24 and 48 h postoperatively [1,17,22]. A recent study by Carruthers et al showed that microvascular issues become visible during clinical evaluation in the initial 23 h following reconstructive surgery [23], suggesting that a 24-h time window should be adequate. These results in combination with the results of the current study suggest that continuous postoperative monitoring of the DIEP flap with the use of tissue oximetry for longer than 24 h would not provide additional important information and therefore a timeframe of 24 h of continuous postoperative tissue oximetry monitoring could be justified.…”
Section: Resultsmentioning
confidence: 99%
“…Other groups have also suggested this optimal time point as well in their institution's experiences with tissue oximetry. [21][22][23] Tissue oximetry facilitated timely takeback in 5 of 9 patients. The other 4 patients had clear clinical signs of flap compromise in the PACU.…”
Section: Discussionmentioning
confidence: 99%
“…Ein engmaschiges postoperatives Monitoring der Lappenplas tik sollte für 24 Stunden durchgeführt werden -idealerweise auf einer intensivmedizinisch betreuten Station. Dies beinhaltet die klinische und stabdopplerunterstützte Kontrolle [29]. Sollte im Rahmen einer lappenplastischen Revision ein Verlust festzustel len sein, muss eine erneute freie lappenplastische Deckung kri tisch evaluiert und ggf.…”
Section: Besondere Aspekte Der Brustrekonstruktion -Konsensusunclassified